Measurement of B(Ds+ -> l plus v) and the decay constant fDs+ from 600 pb(-1) of e(+)e(-) annihilation data near 4170 MeV - Alexander, J; Cassel, D; Duboscq, J; Ehrlich, R; Fields, L; Galik, R; Gibbons, L; Gray, R; Gray, S; Hartill, D; Heltsley, B; Hertz, D; et al. (2009)
We examine e+e-→Ds-Ds*+ and Ds*-Ds+ interactions at 4170 MeV using the CLEO-c detector in order to measure the decay constant fDs+ with good precision. Previously our measurements were substantially higher than the most precise lattice based QCD calculation of (241± 3)MeV. Here we use the Ds+→+ν channel, where the + designates either a μ+ or a τ+, when the τ+→π+ν̄. Analyzing both modes independently, we determine B(Ds+→μ+ν)=( 0.565±0.045±0.017)%, and B(Ds+→τ+ν)=(6.42±0.81± 0.18)%. We also analyze them simultaneously to find an effective value of Beff(Ds+→μ+ν)=(0.591± 0.037±0.018)% and fDs+=( 263.3±8.2±3.9)MeV. Combining with the CLEO-c value determined independently using Ds+→τ+ν, τ+→e+νν̄ decays, we extract fDs+=( 259.5±6.6±3.1)MeV. Combining with our previous determination of B(D+→μ+ν), we extract the ratio fDs+/fD+=1.26±0.06±0.02. No evidence is found for a CP asymmetry between Γ(Ds+→μ+ν) and Γ(Ds-→μ-ν); specifically the fractional difference in rates is measured to be (4.8±6.1)%. Finally, we find B(Ds+→e+ν)<1.2×10-4 at 90% confidence level. © 2009 The American Physical Society.